INDOOR ENVIRONMENTAL QUALITY EFFECT ANALYSIS IN GREEN AND NON-GREEN OFFICE BUILDING TO STAFF’S PERFORMANCE AND SATISFACTION IN SURABAYA - Elvina Shanggrama Wijaya; Jimmy Priatman; Jani Rahardjo (Advances in Civil Engineering and Sustainable Architecture, 2022)
The energy efficiency in an office building can decrease the company’s operational cost. Even so, the operational cost for staff is still larger than the cost for energy. It is important to reassure that the impact given by the building’s indoor environmental quality (IEQ) is positive to staff. This research focusses on two office building in Surabaya, one of them is designed using the green principles and calculations, and the other is not. The building’s IEQ aspects being inspected includes indoor air quality, thermal, lighting, acoustics and layout. A questionnaire survey was held to obtain the reaction from the full time staff regarding the building’s IEQ performance, their satisfaction to it and their self-assessed performance. There are IEQ aspects that affects staff’s performance and satisfaction significantly. The IEQ mean score differs significantly in green and non-green building, but the mean difference in satisfaction and performance were found not significant.